KEWASPADAAN BERKENDARA DAN KECELAKAAN KERJA PADA PENGEMUDI OJEK ONLINE DRIVING AWARENESS AND WORKPLACE ACCIDENT AMONG MOTORCYCLE TAXI DRIVERS - muhammad muin; Noviana Rohmah (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Prevalence of workplace accident among online motorcycle taxi driver was quiet high. Worplace accident may cause injury, disability, death, and decrease of productivity. Many factors contribute to cause accident among online motorcycle taxi driver, one of them was driving awareness. This study aimed to investigate correlation between driving awareness and worplace accident among online motorcycle taxi drivers. It is correlative descriptive quantitative method. Data of driving awareness gathered by situational awareness questionnaire. Data of worplace accident gathered by short answer questionnaire. The Population was online motorcycle taxi drivers who were operating around Tembalang Semarang City, sample taken with convenient sampling consist of 290 drivers. Cross tabulation among driving awareness and workplace accident presented by a table. Correlative analysis with Sommers’ d test to know correlation between driving awareness and workplace accident. Result showed that 41 (28,9 %) drivers performing bad driving awarenes experience no accident, 78 (54,9 %) near miss, and 23 (16,2 %) accident; 58 (49,6 %) drivers performing sufficient driving awarenes experience no accident, 42 (35,9 %) near miss, and 17 (14,5 %) accident; while 24 (77,4%) drivers performing good driving awarenes experience no accident, 6 (19,4%) near miss, and 1 (3,2%) accident. Sommers’ d test showed the coefficient correlation was 0,24, means there is correlation between driving awarenes and workplace accident among online motorcycle taxi drivers. Drivers and the company should doing efforts to prevent workplace accident in order to maintain safety and productivity, one of them by performing good driving awareness during working.